State of infantile mortality in Chernigov area - Ponomarenko N.P.; Garkavy S.I.; Korshun M.M. (Medičnì Perspektivi)
State and dynamics of perinatal and infant mortality rate in Chernigov region over the 2001-2010 period were studied. It is shown that the level of perinatal mortality and mortinatality should be analysed separately over 2 periods: 2001-2006 and 2007-2010, as in 2007 Ukraine turned to determination of perinatal period, live birth - and mortinatality according to WHO criteria. It is identified that over the 2001-2006 period there were no considerable changes of perinatal mortality level in Chernigov region. Over the 2007-2010 period this index dropped by 14 %, while in Ukraine – only by 6,3 %. During 2001-2006 mortinatality in this area was lower than in Ukraine, however it had a tendency to increase (by 10,6%); in subsequent years this resulted in exceeding of national values. Level of mortinatality rate in Chernigov region over the 2001-2010 period dropped by 28,6%, while in Ukraine – by 19,5%. It is identified that decrease in level of mortinatality occurred due to the decline of both neonatal and postneonatal mortality rate. Ranking of region areas by the levels of perinatal mortality, mortinatality, infant mortality, including neonatal and postneonatal mortality was conducted. It is found that perinatal states, inborn anomalies and accidents are the main causes of infant mortality both in Chernigov region and in Ukraine as a whole. Over the 2004-2010 period proportion of perinatal states in the structure of infant mortality rate increased by 14,8 %.